Loyalty is a measure of the success of a company in satisfying customers with the products or services they offer. Bank as a financial institution that takes everyone always competed to develop innovative new service products to entice consumers to make a - Mario Eka Darma Putra (Kompetensi (Competence : Journal of Management Studies), 2016)
Loyalty is a measure of the success of a company in satisfying customers with the products or services they offer. Bank as a financial institution that takes everyone always competed to develop innovative new service products to entice consumers to make a purchase. Consumer banks always want something practical and fast in the process of their business transactions, therefore the effectiveness of e-servqual to note the features of e-banking as one of the keys to making a consumer be loyal. In this article will discuss about how effective use of e-servqual towards the establishment of a consumer satisfaction and loyalty in the use of e-banking products.